2004
DOI: 10.1023/b:trop.0000040935.87175.bb
|View full text |Cite
|
Sign up to set email alerts
|

Risk Indicators Associated with Subclinical Mastitis in Smallholder Dairy Cows in Tanzania

Abstract: Smallholder dairy farmers in Tanzania appear to be unaware of the subclinical mastitis situation in their cows. A cross-sectional study was carried out between June and September 2002 on smallholder dairy herds in the Dar es Salaam region. The study objectives were to establish the prevalence of subclinical mastitis and related risk indicators, and to assess their contribution to the occurrence of subclinical mastitis. Three field procedures based on the principles of herd health and production management were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
37
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 4 publications
12
37
2
Order By: Relevance
“…Compared to individual milk samples, composite milk samples may be less effective for the isolation of micro-organisms due to the dilution factor from uninfected quarters. The prevalence of clinical mastitis in our study (4.8%) is within the range of other reports from smallholder dairy farms in some countries in Sub-Saharan Africa (Abera et al 2011;Getahun et al 2008;Kivaria et al 2004). This provides further support of other studies in the region, which have concluded that sub-clinical mastitis is more prevalent than clinical mastitis (Almaw, Zerihun & Asfaw 2008;Lakew, Tolosa & Tigre 2009).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Compared to individual milk samples, composite milk samples may be less effective for the isolation of micro-organisms due to the dilution factor from uninfected quarters. The prevalence of clinical mastitis in our study (4.8%) is within the range of other reports from smallholder dairy farms in some countries in Sub-Saharan Africa (Abera et al 2011;Getahun et al 2008;Kivaria et al 2004). This provides further support of other studies in the region, which have concluded that sub-clinical mastitis is more prevalent than clinical mastitis (Almaw, Zerihun & Asfaw 2008;Lakew, Tolosa & Tigre 2009).…”
Section: Discussionsupporting
confidence: 72%
“…In individual cows, the prevalence of sub-clinical mastitis recorded during the present study is comparable to that reported from other smallholder farming sectors Harouna et al 2009;Karimuribo et al 2008;Kivaria, Noordhuizen & Kapaga 2004). Compared to individual milk samples, composite milk samples may be less effective for the isolation of micro-organisms due to the dilution factor from uninfected quarters.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In this study, the prevalence of subclinical mastitis in cross and local breeds at cow level were 50.6% and 34.4% respectively whereas prevalence of clinical mastitis in cross and local breeds were 51.5% and 21.5% respectively. this report is lower as compared to the findings of [29] in smallholder dairy farms in Tanzania who reported prevalence of 90.3% and in cross breeds of cows…”
Section: Discussioncontrasting
confidence: 53%